2003
DOI: 10.1046/j.1533-2500.2003.03028.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Mode Radiofrequency Lesioning to Treat Chronic Post‐tonsillectomy Pain (Secondary Glossopharyngeal Neuralgia)

Abstract: Glossopharyngeal neuralgia (GPN) is an uncommon orofacial pain syndrome. Primary GPN is idiopathic, whereas secondary GPN has identifiable causes: tonsillectomy, peritonsillar abscesses, invasive cancer, and trauma. Despite these differences, both types of GPN present similarly and can recur. Pulsed mode radiofrequency lesioning is a safe, non-destructive treatment method and hence, useful in neuropathic pain conditions. We present the first case of chronic post-tonsillectomy pain (secondary glossopharyngeal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
(85 reference statements)
0
23
0
Order By: Relevance
“…Few case reports have shown the efficacy of PRF ablation in GPN. Shah et al (6) presented the first case report of post tonsillectomy chronic GPN successfully treated with PRF ablation. Another case reports published by Abejon (7) and Chua et al (8) also revealed the efficacy of PRF ablation of glossopharyngeal nerve in non-cancer patients.…”
Section: Prf Of Glossopharyngeal Nervementioning
confidence: 99%
“…Few case reports have shown the efficacy of PRF ablation in GPN. Shah et al (6) presented the first case report of post tonsillectomy chronic GPN successfully treated with PRF ablation. Another case reports published by Abejon (7) and Chua et al (8) also revealed the efficacy of PRF ablation of glossopharyngeal nerve in non-cancer patients.…”
Section: Prf Of Glossopharyngeal Nervementioning
confidence: 99%
“…Currently, RF and PRF are used for the treatment of facet joint disease (11), radicular pain (11,12), sacroiliac joint disease (11), and trigeminal (11,13) and other neuralgias (1418). Overall, there is a decreased incidence of side effects and complications from PRF when compared to RF treatment (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found 18 case reports and case series including a total of 105 patients: two cases with glossopharyngeal neuralgia [48] and one case of chronic post‐tonsillectomy pain [49], one post‐traumatic headache [50], three patients with groin pain and orchialgia [51], four patients with chronic back pain syndromes [24], seven patients with occipital neuralgia [52], eight patients with SIJ pain [53], and 39 patients with discogenic pain responsive to L2 DRG block [54]. Other abstracts reported on cases with meralgia paresthesia [55], neuropathic pain [56], postherpetic neuralgia of head and face [57], complicated whiplash [58], and suprascapular nerve for shoulder pain [59].…”
Section: Resultsmentioning
confidence: 99%